2001
DOI: 10.1080/09544120020010093
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between service providers’ personality and customers’ perceptions of service quality across gender

Abstract: The main objective of this paper is to examine the relationship between the personality of the service providers and the service quality performance they provide. The Five-Factor model of personality and the SERVQUAL model of service quality were used to substantiate the hypothesized relationship. Empirical data from 143 pairs of employees and customers indicate that employees with diVerent personality traits perform diVerently on customers' perception of service quality. The results indicated that openness co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 31 publications
0
63
1
Order By: Relevance
“…They are more prone to exhibit customeroriented behavior. The term conscientiousness refers to employees who are hardworking, organized, reliable, thorough, efficient, persistent and attentive to their work [20]. Nurses who are conscientiousness are good at depersonalizing stressful patient encounters and do not let this experience affect their daily job performance.…”
Section: B Personality Traits and Customer-oriented Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…They are more prone to exhibit customeroriented behavior. The term conscientiousness refers to employees who are hardworking, organized, reliable, thorough, efficient, persistent and attentive to their work [20]. Nurses who are conscientiousness are good at depersonalizing stressful patient encounters and do not let this experience affect their daily job performance.…”
Section: B Personality Traits and Customer-oriented Behaviormentioning
confidence: 99%
“…Nurses who possess this trait will display more customer-oriented behavior because they are kind, forgiving, sympathetic and tolerant. Neuroticism refers to an individual's emotional condition where it is related with depressed, worried, angry and unstable [20]. Neurotic nurses treat emotionally stressful encounters as personal attack and easily bothered [23].…”
Section: B Personality Traits and Customer-oriented Behaviormentioning
confidence: 99%
“…Spathis, Petridou and Glaveli (2004) found that male clients of Greek banks have a more positive perception of the quality of service they receive than do women clients. Also, there are several other examples in the marketing literature that indicate that female customers tend to rate service quality lower when comparison is made for both genders (Lin et al, 2001;Tan & Kek, 2004;Juwaheer, 2011).…”
Section: Gender and Service Quality Perceptionsmentioning
confidence: 99%
“…Recently, however, some reseachers have attempted to examine explicitly possible linkages between service quality and personality traits of the employees who deliver the services. Lin, Chiu, and Hsieh (2001) found supporting results for such linkages when they studied service quality in four service sectors in Taiwan. However, Al-Mutawa and Ibrahim (2013) found no such linkages when they studied service quality in four Islamic banks in the UAE and they concluded that these effects might be dependent on other factors such as culture, research design, or industry characteristics.…”
Section: Introductionmentioning
confidence: 63%
“…Regression models were employed to determine the relationship between the five factors of personality traits and overall service quality and its dimensions.The study provided evidence indicating that personality traits do not have their own independent effects on customers' perceptions of Islamic bank service quality. Although Lin et al (2001) found supporting results for such linkages when they studied service quality in four service sectors (not including banks) in Taiwan. Al-Mutawa and Ibrahim (2013) concluded that these effects may be dependent on other factors such as culture, research design, or industry characteristics.…”
Section: Service Qualitymentioning
confidence: 93%